2018
DOI: 10.1093/sp/jxy032
|View full text |Cite
|
Sign up to set email alerts
|

Gender Wage Inequalities Between Historical Heritage and Structural Adjustments: A German–German Comparison Over Time

Abstract: While research on the gender pay gap (GPG) is growing, there is little evidence on the stability or convergence of GPGs against the backdrop of sudden historical changes. Taking advantage of German reunification, after which western male-breadwinner policies were superimposed on the hitherto gender egalitarian East, we illuminate this research gap. Using decompositions on the Socio-economic Panel, we examine how historically grown gender arrangements influence the GPG in eastern and western Germany 1990–2013. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
2
13
0
2
Order By: Relevance
“…Gender disparities in the wagedeterminants are partialled out of the gender coecient β and its random slope γ c . Corresponding to previous evidence (Achatz et al 2005, Minkus andBusch-Heizmann 2018), accounting for gender disparities in full-time employment, working experience and other human capital variables in Model 2 cuts the gender pay gap in half since these are all positively associated with individual 7 However, the coecient of gender ideologies indicates that with each standard deviation towards more traditional gender ideologies, the share of female employees in an industries decreases on average by 1.907 percentage points. Hence, traditional gender beliefs seems to hamper the labor force participation of women (see also Uunk and Lersch 2019).…”
Section: Unveiling Indirect and Direct Channelssupporting
confidence: 60%
See 2 more Smart Citations
“…Gender disparities in the wagedeterminants are partialled out of the gender coecient β and its random slope γ c . Corresponding to previous evidence (Achatz et al 2005, Minkus andBusch-Heizmann 2018), accounting for gender disparities in full-time employment, working experience and other human capital variables in Model 2 cuts the gender pay gap in half since these are all positively associated with individual 7 However, the coecient of gender ideologies indicates that with each standard deviation towards more traditional gender ideologies, the share of female employees in an industries decreases on average by 1.907 percentage points. Hence, traditional gender beliefs seems to hamper the labor force participation of women (see also Uunk and Lersch 2019).…”
Section: Unveiling Indirect and Direct Channelssupporting
confidence: 60%
“…However, accounting for spatial dependence does not aect the overall conclusions. Finally, previous research has indicated regional variation of gender pay gaps between East and West Germany (Minkus and Busch-Heizmann 2018) and by urbanity (Nisic 2017). While my previous analyses adjust for potential dierences in average wages, I also calculated separated models for each part of Germany and included cross-level interactions by urbanity to take into account potential dierences in the gender slope across both dimensions.…”
Section: Robustness Checksmentioning
confidence: 99%
See 1 more Smart Citation
“…As partners are assumed to have a joint utility function with a stable specialization in either paid work or unpaid care work, the person with the higher earnings potential specializes in paid work and provides the household’s income, whereas the person with the lower earnings potential specializes in care and household obligations and is only—if at all—marginally employed (Becker, 1993). Since women’s wages are, on average, lower than men’s (Minkus & Busch-Heizmann, 2018), it is usually the women who invest less in their occupational career and specialize in household production and unpaid caregiving tasks (Aisenbrey & Fasang, 2017). However, it might not only be specialization why women ‘opt’ to work reduced hours or to stay out of work after family care has terminated, but also other factors related to labor market and health consequences of caregiving.…”
Section: Introductionmentioning
confidence: 99%
“…While such policies apply nation-wide, counties differ in their provision of public child-care, which has been considerably expanded since the mid-2000s (Zoch and Schober 2018). The policies and ideological importance within Germany can be highlighted by disparities between East Germany (former German Democratic Republic) and West Germany, with greater public child care provision and more egalitarian gender ideologies in East Germany prompting smaller gender pay gaps than those in West Germany (Achatz et al 2005;Minkus and Busch-Heizmann 2018). Further, research has found that women in rural areas are more disadvantaged than women in urban areas (Hirsch et al 2013;Nisic 2017), and using fine-grained administrative counties, Fuchs et al (2019) reveal most comprehensively that gender pay gaps vary subnationally within Germany.…”
Section: Introductionmentioning
confidence: 99%